2017
DOI: 10.1038/srep45675
|View full text |Cite
|
Sign up to set email alerts
|

Visual deprivation selectively reshapes the intrinsic functional architecture of the anterior insula subregions

Abstract: The anterior insula (AI) is the core hub of salience network that serves to identify the most relevant stimuli among vast sensory inputs and forward them to higher cognitive regions to guide behaviour. As blind subjects were usually reported with changed perceptive abilities for salient non-visual stimuli, we hypothesized that the resting-state functional network of the AI is selectively reorganized after visual deprivation. The resting-state functional connectivity (FC) of the bilateral dorsal and ventral AI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 83 publications
(150 reference statements)
1
14
1
Order By: Relevance
“…The right AI has been confirmed to be a functional hub in coordinating brain networks to produce adaptive behavior, especially the modulation in the DMN and DAN (Wang et al, 2018), as suggested in our study. A weakened functional connection in the early deprivation subject was discovered between the subregions of AI (Nomi et al, 2016; Liu et al, 2017), as the reduced connection from left AI to right AI in our study. Abnormalities within the IPL have been associated with working memory dysfunction as well as impairments in cognitive insight and reality perception (Guo et al, 2014; Lee et al, 2015; Chahine et al, 2017).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…The right AI has been confirmed to be a functional hub in coordinating brain networks to produce adaptive behavior, especially the modulation in the DMN and DAN (Wang et al, 2018), as suggested in our study. A weakened functional connection in the early deprivation subject was discovered between the subregions of AI (Nomi et al, 2016; Liu et al, 2017), as the reduced connection from left AI to right AI in our study. Abnormalities within the IPL have been associated with working memory dysfunction as well as impairments in cognitive insight and reality perception (Guo et al, 2014; Lee et al, 2015; Chahine et al, 2017).…”
Section: Discussionsupporting
confidence: 53%
“…Our findings suggest that the specific abnormalities of the AI and general alterations within the IPL may be mediated by inhibitory interactions from other regions of the left dorsal attention network. A recent study in EB subjects also suggested that early visual deprivation can selectively reshape the functional architecture of the salience network (Liu et al, 2017). Our study found that most of the effective connections were decreased in the EB subjects, suggesting a corresponding reorganization of the human brain due to the early deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al, 2007;Wang et al, 2013;Yu et al, 2008). By contrast, resting-state synchrony between "visual" cortices and frontal-parietal cortices is increased in blindness (Bedny et al, 2011;Bedny, Konkle, Pelphrey, Saxe, & Pascual-Leone, 2010;Burton et al, 2014;Deen, Saxe, & Bedny, 2015;L. Liu et al, 2017;Y.…”
Section: Insights Into the Relationship Of Connectivity And Function mentioning
confidence: 99%